2020
DOI: 10.1177/2192568219868475
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Blood Loss in Spine Surgery

Abstract: Study Design: Broad narrative review. Objective: To review and summarize the current literature on guidelines, outcomes, techniques and indications surrounding multiple modalities of minimizing blood loss in spine surgery. Methods: A thorough review of peer-reviewed literature was performed on the guidelines, outcomes, techniques, and indications for multiple modalities of minimizing blood loss in spine surgery. Results: There is a large body of literature that provides a consensus on guidelines regarding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 124 publications
0
59
1
Order By: Relevance
“…Although blood loss is the common cause of acute haemodynamic instability in spine surgery,[ 1 ] in our case a normal haemoglobin level after blood transfusion does not support this diagnosis. Other probable differential diagnoses include dural traction leading to vasovagal response.…”
contrasting
confidence: 68%
“…Although blood loss is the common cause of acute haemodynamic instability in spine surgery,[ 1 ] in our case a normal haemoglobin level after blood transfusion does not support this diagnosis. Other probable differential diagnoses include dural traction leading to vasovagal response.…”
contrasting
confidence: 68%
“…36 Due to the increased overall perioperative risk associated with ABTs in spine surgery, as well as the intraoperative anesthesiological challenges in fluid and coagulation management, various strategies have aimed to decrease intraoperative blood loss in oncological spine surgery. 37 The literature shows that preoperative embolization 38,39 and use of antifibrinolytic agents, 40,41 or even rare invasive approaches, such as aortic balloon occlusion, 42,43 applied to decrease intraoperative blood loss. For adaptation of the surgical strategy by using minimally invasive or staged surgical approaches, embolization is the preoperative procedure that is most widely used at high-volume oncological spine centers, and a large retrospective review by Nair et al demonstrated that preoperative embolization can be safely applied.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative methods to control blood loss include positioning to reduce intraabdominal pressure, the use of tranexamic acid and the use of topical anti brinolytic agents. Moreover, modi ed anesthesia techniques such as core temperature control and hypotensive anesthesia have shown promising results in safely reducing blood loss [30][31][32].…”
Section: Factors In Uencing Intraoperative Blood Lossmentioning
confidence: 99%